MODEL ECONOMIC PRODUCTION QUANTITY (EPQ) UNTUK PERENCANAAN TERKOORDINASI PADA PRODUK DENGAN BACKORDER PARSIAL DAN KOMPONENNYA - Oktavia, Ayu; Djuwandi, Djuwandi; Khabibah, Siti (MATEMATIKA, 2017)
Economic Production Quantity (EPQ) used to determined policy and oversee inventory levels. This article discussed on EPQ models for Â planed of product with partial backordered and its component. The final product is assummed have m component and coordinated planning used to coordinate component of product and final product which is the components used for basic EPQ models and for final product planned using partial backorder EPQ. Numerical simulation given based Â data on UD. Adi Mulya.